Head movements during two computer work tasks assessed by accelerometry. - Bernmark E; Forsman M; Wiktorin C; Bernmark, Eva; Forsman, Mikael; Wiktorin, Christina (Applied Ergonomics, 2011)
We investigated whether potential differences in head inclinations and accelerations for two highly similar computer work tasks could be detected using (1) a triaxial accelerometer and (2) a simulated uniaxial accelerometer. Ten subjects' head movements were registered with a triaxial accelerometer system for two similar document-management tasks at their work place: a fully electronic document-management task and one also involving paper documents. In situations where head movements were small, a triaxial accelerometer was able to discriminate between the different degrees of static work of the neck in terms of range of head inclinations and accelerations. A difference in head acceleration was also found by using a simulated uniaxial accelerometer. Thus, in terms of head movement and for work similar to this office work, potential dynamic differences in observationally similar work tasks can be investigated by using a triaxial accelerometer. For acceleration alone, a uniaxial accelerometer can also be used.